Exploring the determinants of perceived risk of middle east respiratory syndrome (MERS) in Korea - Kim, Sunhee; Kim, Seoyong (International Journal of Environmental Research and Public Health, 2018)
The world is turning into a risky society. Although modernization based on the developments in science and technology has increased individuals’ well-being and wealth, the perceived risk toward the complex technological system has increased. In a risky society, social accidents amplify the existing fear among individuals. It is generally assumed that each value, perception, and resource influences the fear of risk. However, very few studies have tested these three factors together within an integrated causal model. Therefore, the present study aimed to examine the determinants that influence the perceived risk in cases of Middle East Respiratory Syndrome (MERS), a deadly epidemic disease, in Korea. Based on the theoretical model, we analyzed the survey data collected from respondents (N = 814) in Korea. After controlling for variables such as sociodemographic characteristics, we examined how three competing factors, i.e., value, perception, and resource, influence the perceived risk of MERS. The analysis showed that trust and vulnerability variables in the perception factor, health state, and perceived knowledge in the resource factor had a significant impact on the perceived risk of MERS.
Keywords: Coronavirus Infections; Disease Outbreaks; Female; Humans; Male; Republic of Korea; Risk Assessment; Risk Factors; Surveys and Questionnaires; Middle east respiratory syndrome; Resource; Risk; Risk communication; Risk perception; Value